2022
DOI: 10.3390/v14102264
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 Toxicity in Yeast Is Associated with a Reduction in Autophagy, and Deletions of TIP41 and PBP1 Counteract These Effects

Abstract: When human TDP-43 is overexpressed in yeast it is toxic and forms cytoplasmic aggregates. The mechanism of this toxicity is unknown. Genetic screens for TDP-43 toxicity modifiers in the yeast system previously identified proteins, including PBP1, that enhance TDP-43 toxicity. The determination in yeast that deletion of PBP1 reduces TDP-43 toxicity while overexpression enhances toxicity, led to the discovery that its human homolog, ATXN2, is associated with ALS risk. Thus, the yeast system has relevance to huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…As seen previously [ 32 ], the overexpression of wild-type TDP-43 significantly reduced autophagy relative to the vector control. Using GFP-ATG8 (Green Fluorescent Protein fused to autophagy-related protein 8) immunoblotting to measure autophagy showed that the expression of the more toxic TDP-43 mutants M322K and W334K reduced autophagy even more than wild-type TDP-43.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As seen previously [ 32 ], the overexpression of wild-type TDP-43 significantly reduced autophagy relative to the vector control. Using GFP-ATG8 (Green Fluorescent Protein fused to autophagy-related protein 8) immunoblotting to measure autophagy showed that the expression of the more toxic TDP-43 mutants M322K and W334K reduced autophagy even more than wild-type TDP-43.…”
Section: Resultssupporting
confidence: 85%
“…The mechanism by which TDP-43 causes toxicity is unknown. However, the expression of TDP-43 reduces autophagy in yeast, and pbp1-Δ and tip41-Δ (target of rapamycin signaling pathway inhibitor protein 41) deletions, which lower TDP-43 toxicity, reverse TDP-43’s effect on autophagy [ 32 ]. While we do not know how TDP-43 affects autophagy, one possibility is that TDP-43’s effect on toxicity and autophagy is due to an effect on TORC1 (target of rapamycin complex 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the yeast S. cerevisiae represents the simplest eukaryotic cell model in which it is possible to recapitulate TDP-43-dependent toxicity and to rapidly assay the impact of disease-associated TDP-43 mutations. Accordingly, yeast models recently became extremely useful to identify many genetic/molecular modifiers (i.e., enhancers and/or suppressors) of the neurotoxicity induced by the ectopic expression of sequences encoding for WT or mutant TDP-43 [25][26][27]30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ectopic expression of human wild-type (WT) or disease-associated mutant forms of TARDBP gene is toxic and forms TDP-43 cytoplasmic aggregates in yeast cells, providing the opportunity to shed light on how the protein may affect cell viability and RNA metabolism [26][27][28]. Moreover, yeast models were successfully applied to perform screening for genetic modifiers or potential therapeutic targets that could influence TDP-43 aggregation and/or toxicity [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PBP1, a yeast homolog of human ataxin 2, was found to increase the risk for ALS significantly and was pinpointed as a critical target for drug development efforts. Additionally, Park et al demonstrated that the yeast gene TIP41 deletion also curtailed TDP-43 toxicity [106]. The beneficial effects of these genes were linked to the activation of autophagy, highlighting potential therapeutic pathways.…”
Section: Yeastmentioning
confidence: 99%